2006
DOI: 10.1016/j.procbio.2006.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Agitation effects on morphology and protein productive fractions of filamentous and pelleted growth forms of recombinant Aspergillus niger

Abstract: Recombinant Aspergillus niger genetically engineered to produce glucose oxidase using the constitutive gpdA promoter and the glucoamylase signal sequence for secretion was grown in batch cultures at agitation speeds of 200 -800 rpm covering the industrial relevant power input range of 0.1 -5 W kg -1 . The growth morphology ranged from large pellets with an average diameter of 1500 µm at low power input up to micropellets embedded in a filamentous network at high power input. A correlation of agitation intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 52 publications
3
28
0
1
Order By: Relevance
“…This finding indicates that the RNA levels of these genes per unit mass of hypha are much higher in zone 4 than in zone 2. In agreement with this, acridine orange staining showed that the periphery of microcolonies of A. niger is rich in RNA, while the center is not (5). Acridine orange binds to single-and double-stranded nucleic acids, resulting in red and green fluorescence, respectively.…”
Section: Vol 77 2011 Heterogeneous Fungal Colonies 1265supporting
confidence: 71%
“…This finding indicates that the RNA levels of these genes per unit mass of hypha are much higher in zone 4 than in zone 2. In agreement with this, acridine orange staining showed that the periphery of microcolonies of A. niger is rich in RNA, while the center is not (5). Acridine orange binds to single-and double-stranded nucleic acids, resulting in red and green fluorescence, respectively.…”
Section: Vol 77 2011 Heterogeneous Fungal Colonies 1265supporting
confidence: 71%
“…Although the highest cell growth was obtained at an agitation speed of 750 rpm, the highest specific and volumetric yield was obtained at an agitation speed of 550 rpm. Our results coincided with the the results of others investigations [32,33]. But, no earlier reports have discussed about the impact of agitation speed on cell growth, plasmid stability, acetate accumulation and rhG-CSF expression [25,26] In the production of rhG-CSF by E. coli BL21 (DE3) PLysS, the relative viscosity of culture broth became steep declined slope (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Other researchers also reported that 100 lm is a limitation distance for mycelium which with biofilm [39]. Investigations have shown that pellet formation is necessary for the production of some enzymes from filamentous microorganisms, such as polygalacturonase [14,37], phytase [16], glucoamylase [8], fructosyltransferase [15], and other proteins [33]. Based on other researchers and their results, Papagianni concluded that such phenomena may be related to diffusional limitations in pellets, which either reduce the extent of catabolic repression in pellets or limit the oxygen supply, preventing oxidative inactivation of a specific set of enzymes [1,8].…”
Section: Morphology and Broth Rheology Study In Strmentioning
confidence: 99%